EXPERIMENTAL OPTIMIZATION OF AERODYNAMIC DRAG COEFFICIENT OF A MINIBUS MODEL WITH NON-SMOOTH SURFACE PLATE APPLICATION - CIHAN BAYINDIRLI; MEHMET CELIK (Journal of Engineering Studies and Research)
In this study non-smooth surface plate application was experimentally investigated to flow control around a scaled minibus model in a wind tunnel. 1/15 scaled minibus model and non-smooth surface plate were designed in SolidWorks® Cad program and produced in 3-D printer. It was focused on decrease of drag coefficient of vehicle with non-smooth surface plate by reducing flow separation. The experimental tests carried out 4 free stream velocities between the speed of 13.90-27.40 m/s and 2.62x105-5.18x105 Reynolds numbers. In wind tunnel tests Reynolds number independence was used to ensure dynamic similarity. The blockage rate was 10.68 %. It was determined that the using of non-smooth surface plate e on the front roof area of minibus model decreased to drag coefficient by an average of 1.03%. This reduction rate can decrease fuel consumption of vehicle about 0.5% at high speeds.